Peramalan Kedatangan Wisatawan Manca Negara Melalui Bandara Husein Sastra Negara Bandung Dengan Menggunakan Metode Arima (Autoregressive Integreted Moving Average) - Waluyo, Jatmiko Edy (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2019)
Data processing and analysis of foreign tourist arrivals in Bandung through Husein Sastra Bandung Airport is very necessary in an effort to take a decision related to tourism planning in Bandung in particular and national tourism generally, be it planning related to the Airport itself and tourism planning In Bandung Raya. The purpose of this study is to determine the mathematical model or good statistical relationship between the predicted variables (the arrival of foreign tourists through the International Airport Husein Sastra Negara Bandung) with the historical value of these variables using the method of forecasting ARIMA (Autoregressive Integrated Moving Average), so that forecasting can Done with the model. ARIMA is often also called the Box-Jenkins time series method. ARIMA is very good for short-term forecasting, while for long-term forecasting the accuracy of forecasting is not good. Usually will tend to flat (flat / constant) for a long period. The results showed that, to know the accuracy of forecasting model in predicting the data, it can be seen the size of precision of forecasting model in table Fit Model, such as: MAPE, MAE, and others. From the results of fit model testing, it can be seen that the value of MAPE of 21.105% and MAE of 2467.875. This shows that the average accuracy rate of the model in predicting the number of foreign tourist arrivals through Husein Sastra Negara Bandung is 78.895%. To know the value of prediction (prediction) in some period to come, can be seen in table Forecast. While to know the fluctuation of data, either that has happened or will be foreseen. From the forecast table can be known the value of the forecast of tourist arrivals. From the table can also be calculated the estimated maximum error value in forecasting, for example for forecasting in June-December 2017, with 95% confidence level, it is estimated that foreign tourist arrivals will not deviate more than 21.105%.